Shares - Veress , Emőd (Joint Stock and Limited Liability Companies in East Central Europe, 2025)
References: Angheni, S. (2013) Drept comercial. Profesionişti-comercianţi. Bucureşti: C.H. Beck. Bieniak, M., Nita-Jagielski, G. (eds.) (2022) Kodeks społek handlowych. Komentarz, 8th edn. Warszawa: C.H. Beck. Bohinc, R. (2008) Korporacije: razlaga pravnih pravil in sodna praksa. Ljubljana: Nebra. Čech, P., Šuk, P. (2016) Pravo obchodnich společnosti: v praxi a pro praxi (nejen soudni). Praha: Bova Polygon. Černá, S. (2015) ‘O nepravých a pravých kusových akciích’, Obchodněpravni revue, 2015/5, pp. 129–134. Černá, S., Štenglová, I., Pelikánová, I. et al. (2021) Pravo obchodnich korporaci, 2nd edn. Praha: Wolters Kluwer. David, S. (2014) in Cărpenaru, St.D., Piperea, Gh., David, S. (eds.) Legea societăților. Comentariu pe articole, 5th edn. București: C.H. Beck. Eichlerová, K. (2022a) ‘Dědění podílu’ in Kotásek, J., Špačková, P. (eds.) Pocta prof. Bejčkovi k 70. Narozeninam, 1st edn. Brno: Masarykova univerzita, pp. 255–274. Fazakas, Z.J. (2020) ‘A társasági szerződés, mint szerződés’, Iustum Aequum Salutare, 2020/3, pp. 63–105. Gál, J. (2022) ‘Egy tag – egy üzletrész? Az egyszemélyes kft. üzletrésze’, Gazdasag es Jog, 2022/5–6, pp. 56–57. Georgescu, I. L. (1948) Drept comercial roman, vol. II. Bucureşti: Ed. Socec. Gheorghe, C. (2020) Tratat de drept comercial roman. București: C.H. Beck. Ivanjko, Š., Kocbek, M., Prelič, S. (2009) Korporacijsko pravo. Ljubljana: GV Založba. Jara, Z. (ed.) (2023) Kodeks społek handlowych. Komentarz. Warszawa: C.H. Beck. Jerzmanowski, J. (2016) Finansowanie przez społkę akcyjną nabycia lub objęcia emitowanych przez nią akcji w procesie wykupu menedżerskiego. Warszawa: C.H. Beck. Jerzmanowski, J., Sójka, T. (2008) ‘“Financial assistance” po nowelizacji kodeksu spółek handlowych’, Przegląd Prawa Handlowego, 2008/11, pp. 9–15. Jovanović, N., Radović, V., Radović, M. (2021) Kompanijsko pravo – Pravo privrednih društava, 2nd edn. Beograd: Pravni fakultet u Beogradu, Centar za izdavaštvo i informisanje. Kidyba, A. (2023) Kodeks społek handlowych. Komentarz. Tom I i II, 18th edn. Warszawa: Wolters Kluwer. Kožiak, J. (2019) ‘Manželské majetkové právo a podíl v obchodní korporaci’, Obchodni pravo, 28(5), pp. 22–34. Kříž, R. (2019) ‘“Tracking” stock aneb divizní akcie jako zvláštní druh akcií’, Obchodněpravni revue, 2019/4, pp. 90–95. Kříž, R. (2022) ‘Akcie s vysílacím právem a změna vnitřní struktury orgánů akciové společnosti’, Bulletin advokacie, (3), pp. 16–19. Kundić, M., Smajla, N. (2020) ‘Utjecaj radničkog dioničarstva na sigurnost i zaštitu na radnom mjestu’, Sigurnost: časopis za sigurnost u radnoj i životnoj okolini, 62(2), pp. 127–137 [Online]. Available at: https://hrcak.srce.hr/240702 (Accessed: 10 October 2025). Kwaśnicki, R.L., Pietrzak, P. (2002) ‘Obrót akcjami i udziałami w świetle regulacji prawa spółek’, Dodatek do Monitora Prawniczego, 2002/23, pp. 17–23. Lála, D. (2020) Druhy podilů v kapitalovych společnostech, 1st edn. Prague: C.H. Beck. Lasák, J., Dědič, J., Pokorná, J., Čáp, Z. et al. (2021) Zakon o obchodnich korporacich. Komentař, 2nd edn. Praha: Wolters Kluwer ČR. Lepetić, J. (2018) ‘Jedna akcija – jedan glas: Da li je vreme za promene?’, Zbornik radova Pravnog fakulteta u Novom Sadu, 52(3) [Online]. Available at: https://doi.org/10.5937/ zrpfns52-19816 (Accessed: 10 October 2025). Lepetić, J. (2019) ‘Dodatni glasovi kao nagrada lojalnim akcionarima: predlog za reformu’, Anali Pravnog fakulteta u Beogradu, 67(1), pp. 392–425. Marjanski, V. (2020) ‘Raspodela dobiti članovima društva sa ograničenom odgovornošću i razlika u odnosu na druge isplate korporativno-pravnog karaktera’, Zbornik radova Pravnog fakulteta u Novom Sadu, 54(1), pp. 215–243 [Online]. Available at: https://doi.org/10.5937/zrpfns54-26336 (Accessed: 10 October 2025). Mazgaj, M. (2023) in Z. Jara (ed.) Kodeks społek handlowych. Komentarz, 4th edn. Warszawa: C.H. Beck/Legalis. Mićović, M. (2016) Privredno pravo, 4th edn. Kragujevac: Pravni fakultet u Kragujevcu, Institut za pravne i društvene nauke. Modzelewska, K., Reszczyk-Król, K. (2023) in Jara, Z. (ed.) Kodeks społek handlowych. Komentarz. Warszawa: C.H. Beck/Legalis. Mrázová, Ž. (2022a) ‘Share transfer restrictions in closely held corporations: shareholders’ protection and exit strategies’, Pravny obzor, 2022/105 (special issue), pp. 29–43. Mrázová, Ž. (2022b) ‘Korporačné obmedzenia prevoditeľnosti účasti na spoločnosti a súhlasy orgánov spoločnosti s prevodom účasti’ in Havel, B., Nevolná, Z. (eds.) Převody obchodnich podilů a akcii. Praha: Wolters Kluwer ČR, pp. 55–73. Mrázová, Ž., in Patakyová, M., Ďurica, M., Husár, J. et al. (2021) Aplikovane pravo obchodnych spoločnosti a družstva – ťažiskove inštituty. Bratislava: Wolters Kluwer SR. Opalski, A. (ed.) (2018) Kodeks społek handlowych. Tom II B. Społka z ograniczoną odpowiedzialnością. Komentarz do art. 227–300. Warszawa: C.H. Beck. Ovečková, O. et al. (2022) Obchodny zakonnik. Veľky komentar, vol. I, 2nd edn. Bratislava: Wolters Kluwer SR. Patakyová, M. et al. (2022) Obchodny zakonnik. Komentar, 1st edn. Bratislava: C.H. Beck. Radović, V. (2007) ‘Pružanje finansijske podrške za sticanje svojih akcija’, Pravni život, 56(12), pp. 183–212. Schiau, I., Prescure, T. (2009) Legea societăţilor comerciale nr. 31/1990. Analize şi comentarii pe articole, 2nd edn. Bucureşti: Editura Hamangiu. Sójka, T. (2020) ‘Dematerializacja akcji niepublicznej spółki akcyjnej’, Monitor Prawniczy, 13, pp. 668–675. Stanciu, D. C., David, S., Predoiu, C., Piperea, G. (2006) Legea societăţilor comerciale. Comentariu pe articole, 3rd edn. Bucureşti: C.H. Beck. Štenglová, I., Šuk, P. (2022) ‘Zvláštní druhy akcií jako nástroj účasti akcionářů na řízení společnosti’, Bulletin advokacie, (7–8), pp. 46–52. Štenglová, I., Dědič, J., Lasák, J., Pihera, V., Lála, D., Josková, L. (2023) Akciove společnosti, 1st edn. Praha: C. H. Beck. Štenglová, I., Havel, B., Cileček, F., Kuhn, P., Šuk, P. (2020) Zakon o obchodnich korporacich. Komentař, 3rd edn. Praha: C. H. Beck. Šuleková, Ž. (2017) ‘Akciová spoločnosť s premenlivým základným imaním – nová forma kolektívneho investovania’, Justična revue, 69(8–9), pp. 997–1008. Szczurowski, T. (2018) ‘Forma umowy rozporządzającej udziałami spółki z o.o.’, Przegląd Ustawodawstwa Gospodarczego, 2018/1, pp. 25–29. Tipurić, D. et al. (2004) ESOP i hrvatsko poduzeće. Zagreb: Sinergija. Török, T. (2022) ‘A törzsbetét, a törzstőke, valamint az üzletrész elsődleges szabályainak változása a magyar társasági jogban’, Gazdasag es Jog, 2022/9–10, pp. 11–19. Turcu, I. (1998) Teoria şi practica dreptului comercial roman, vol. I. Bucureşti: Lumina Lex. Vasiljević, M. (2012) Kompanijsko pravo – pravo privrednih društava, 7th edn. Beograd: Pravni fakultet u Beogradu, Centar za izdavaštvo i informisanje. Veress, E. (2010) ‘Discuţii privind revocarea administratorilor şi transmiterea părţilor sociale la societăţile comerciale cu răspundere limitată’, Dreptul, (9), pp. 96–105. Veress, E. (2019a) ‘Megjegyzések a korlátolt felelősségű társaságok üzletrészének forgalmáról’, Jogtudomanyi Kozlony, 2019/3, pp. 119–125. Veress, E. (2019b) ‘Report from Hungary: Is It Possible to Issue Bearer Shares in Hungary? Remarks on Mandatory and Default Rules in Hungarian Company Law’, European Company Law, 16(3), pp. 95–100. Veress, E. (2024a) ‘Állandó és változó elemek a kft. szabályozásában. 2. rész: Törzsbetét, üzletrész’, Gazdasag es Jog, 2024/11–12, pp. 3–10. Veress, E. (2024b) ‘A társasági jog elmélete és a társaságok általános jellemzői’ in Fegyveresi, Zs. (ed.) Roman tarsasagi jog, 3rd edn. Cluj-Napoca: Forum Iuris. Žitňanská, L. (2022) ‘Účinky prevodu obchodného podielu a akcie medzi zmluvnými stranami, voči spoločnosti a voči veriteľom’ in Havel, B., Nevolná, Z. (eds.) Převody obchodnich podilů a akcii. Praha: Wolters Kluwer ČR, pp. 137–147. Zvára, M. (2017) ‘Nabytí podílu od neoprávněného ve společnosti s ručením omezeným na základě smlouvy o převodu podílu’, Obchodněpravni revue, (7–8), pp. 193–198. References Angheni, S. (2013) Drept comercial. Profesionişti-comercianţi. Bucureşti: C.H. Beck. Bieniak, M., Nita-Jagielski, G. (eds.) (2022) Kodeks społek handlowych. Komentarz, 8th edn. Warszawa: C.H. Beck. Bohinc, R. (2008) Korporacije: razlaga pravnih pravil in sodna praksa. Ljubljana: Nebra. Čech, P., Šuk, P. (2016) Pravo obchodnich společnosti: v praxi a pro praxi (nejen soudni). Praha: Bova Polygon. Černá, S. (2015) ‘O nepravých a pravých kusových akciích’, Obchodněpravni revue, 2015/5, pp. 129–134. Černá, S., Štenglová, I., Pelikánová, I. et al. (2021) Pravo obchodnich korporaci, 2nd edn. Praha: Wolters Kluwer. David, S. (2014) in Cărpenaru, St.D., Piperea, Gh., David, S. (eds.) Legea societăților. Comentariu pe articole, 5th edn. București: C.H. Beck. Eichlerová, K. (2022a) ‘Dědění podílu’ in Kotásek, J., Špačková, P. (eds.) Pocta prof. Bejčkovi k 70. Narozeninam, 1st edn. Brno: Masarykova univerzita, pp. 255–274. Fazakas, Z.J. (2020) ‘A társasági szerződés, mint szerződés’, Iustum Aequum Salutare, 2020/3, pp. 63–105. Gál, J. (2022) ‘Egy tag – egy üzletrész? Az egyszemélyes kft. üzletrésze’, Gazdasag es Jog, 2022/5–6, pp. 56–57. Georgescu, I. L. (1948) Drept comercial roman, vol. II. Bucureşti: Ed. Socec. Gheorghe, C. (2020) Tratat de drept comercial roman. București: C.H. Beck. Ivanjko, Š., Kocbek, M., Prelič, S. (2009) Korporacijsko pravo. Ljubljana: GV Založba. Jara, Z. (ed.) (2023) Kodeks społek handlowych. Komentarz. Warszawa: C.H. Beck. Jerzmanowski, J. (2016) Finansowanie przez społkę akcyjną nabycia lub objęcia emitowanych przez nią akcji w procesie wykupu menedżerskiego. Warszawa: C.H. Beck. Jerzmanowski, J., Sójka, T. (2008) ‘“Financial assistance” po nowelizacji kodeksu spółek handlowych’, Przegląd Prawa Handlowego, 2008/11, pp. 9–15. Jovanović, N., Radović, V., Radović, M. (2021) Kompanijsko pravo – Pravo privrednih društava, 2nd edn. Beograd: Pravni fakultet u Beogradu, Centar za izdavaštvo i informisanje. Kidyba, A. (2023) Kodeks społek handlowych. Komentarz. Tom I i II, 18th edn. Warszawa: Wolters Kluwer. Kožiak, J. (2019) ‘Manželské majetkové právo a podíl v obchodní korporaci’, Obchodni pravo, 28(5), pp. 22–34. Kříž, R. (2019) ‘“Tracking” stock aneb divizní akcie jako zvláštní druh akcií’, Obchodněpravni revue, 2019/4, pp. 90–95. Kříž, R. (2022) ‘Akcie s vysílacím právem a změna vnitřní struktury orgánů akciové společnosti’, Bulletin advokacie, (3), pp. 16–19. Kundić, M., Smajla, N. (2020) ‘Utjecaj radničkog dioničarstva na sigurnost i zaštitu na radnom mjestu’, Sigurnost: časopis za sigurnost u radnoj i životnoj okolini, 62(2), pp. 127–137 [Online]. Available at: https://hrcak.srce.hr/240702 (Accessed: 10 October 2025). Kwaśnicki, R.L., Pietrzak, P. (2002) ‘Obrót akcjami i udziałami w świetle regulacji prawa spółek’, Dodatek do Monitora Prawniczego, 2002/23, pp. 17–23. Lála, D. (2020) Druhy podilů v kapitalovych společnostech, 1st edn. Prague: C.H. Beck. Lasák, J., Dědič, J., Pokorná, J., Čáp, Z. et al. (2021) Zakon o obchodnich korporacich. Komentař, 2nd edn. Praha: Wolters Kluwer ČR. Lepetić, J. (2018) ‘Jedna akcija – jedan glas: Da li je vreme za promene?’, Zbornik radova Pravnog fakulteta u Novom Sadu, 52(3) [Online]. Available at: https://doi.org/10.5937/ zrpfns52-19816 (Accessed: 10 October 2025). Lepetić, J. (2019) ‘Dodatni glasovi kao nagrada lojalnim akcionarima: predlog za reformu’, Anali Pravnog fakulteta u Beogradu, 67(1), pp. 392–425. Marjanski, V. (2020) ‘Raspodela dobiti članovima društva sa ograničenom odgovornošću i razlika u odnosu na druge isplate korporativno-pravnog karaktera’, Zbornik radova Pravnog fakulteta u Novom Sadu, 54(1), pp. 215–243 [Online]. Available at: https://doi.org/10.5937/zrpfns54-26336 (Accessed: 10 October 2025). Mazgaj, M. (2023) in Z. Jara (ed.) Kodeks społek handlowych. Komentarz, 4th edn. Warszawa: C.H. Beck/Legalis. Mićović, M. (2016) Privredno pravo, 4th edn. Kragujevac: Pravni fakultet u Kragujevcu, Institut za pravne i društvene nauke. Modzelewska, K., Reszczyk-Król, K. (2023) in Jara, Z. (ed.) Kodeks społek handlowych. Komentarz. Warszawa: C.H. Beck/Legalis. Mrázová, Ž. (2022a) ‘Share transfer restrictions in closely held corporations: shareholders’ protection and exit strategies’, Pravny obzor, 2022/105 (special issue), pp. 29–43. Mrázová, Ž. (2022b) ‘Korporačné obmedzenia prevoditeľnosti účasti na spoločnosti a súhlasy orgánov spoločnosti s prevodom účasti’ in Havel, B., Nevolná, Z. (eds.) Převody obchodnich podilů a akcii. Praha: Wolters Kluwer ČR, pp. 55–73. Mrázová, Ž., in Patakyová, M., Ďurica, M., Husár, J. et al. (2021) Aplikovane pravo obchodnych spoločnosti a družstva – ťažiskove inštituty. Bratislava: Wolters Kluwer SR. Opalski, A. (ed.) (2018) Kodeks społek handlowych. Tom II B. Społka z ograniczoną odpowiedzialnością. Komentarz do art. 227–300. Warszawa: C.H. Beck. Ovečková, O. et al. (2022) Obchodny zakonnik. Veľky komentar, vol. I, 2nd edn. Bratislava: Wolters Kluwer SR. Patakyová, M. et al. (2022) Obchodny zakonnik. Komentar, 1st edn. Bratislava: C.H. Beck. Radović, V. (2007) ‘Pružanje finansijske podrške za sticanje svojih akcija’, Pravni život, 56(12), pp. 183–212. Schiau, I., Prescure, T. (2009) Legea societăţilor comerciale nr. 31/1990. Analize şi comentarii pe articole, 2nd edn. Bucureşti: Editura Hamangiu. Sójka, T. (2020) ‘Dematerializacja akcji niepublicznej spółki akcyjnej’, Monitor Prawniczy, 13, pp. 668–675. Stanciu, D. C., David, S., Predoiu, C., Piperea, G. (2006) Legea societăţilor comerciale. Comentariu pe articole, 3rd edn. Bucureşti: C.H. Beck. Štenglová, I., Šuk, P. (2022) ‘Zvláštní druhy akcií jako nástroj účasti akcionářů na řízení společnosti’, Bulletin advokacie, (7–8), pp. 46–52. Štenglová, I., Dědič, J., Lasák, J., Pihera, V., Lála, D., Josková, L. (2023) Akciove společnosti, 1st edn. Praha: C. H. Beck. Štenglová, I., Havel, B., Cileček, F., Kuhn, P., Šuk, P. (2020) Zakon o obchodnich korporacich. Komentař, 3rd edn. Praha: C. H. Beck. Šuleková, Ž. (2017) ‘Akciová spoločnosť s premenlivým základným imaním – nová forma kolektívneho investovania’, Justična revue, 69(8–9), pp. 997–1008. Szczurowski, T. (2018) ‘Forma umowy rozporządzającej udziałami spółki z o.o.’, Przegląd Ustawodawstwa Gospodarczego, 2018/1, pp. 25–29. Tipurić, D. et al. (2004) ESOP i hrvatsko poduzeće. Zagreb: Sinergija. Török, T. (2022) ‘A törzsbetét, a törzstőke, valamint az üzletrész elsődleges szabályainak változása a magyar társasági jogban’, Gazdasag es Jog, 2022/9–10, pp. 11–19. Turcu, I. (1998) Teoria şi practica dreptului comercial roman, vol. I. Bucureşti: Lumina Lex. Vasiljević, M. (2012) Kompanijsko pravo – pravo privrednih društava, 7th edn. Beograd: Pravni fakultet u Beogradu, Centar za izdavaštvo i informisanje. Veress, E. (2010) ‘Discuţii privind revocarea administratorilor şi transmiterea părţilor sociale la societăţile comerciale cu răspundere limitată’, Dreptul, (9), pp. 96–105. Veress, E. (2019a) ‘Megjegyzések a korlátolt felelősségű társaságok üzletrészének forgalmáról’, Jogtudomanyi Kozlony, 2019/3, pp. 119–125. Veress, E. (2019b) ‘Report from Hungary: Is It Possible to Issue Bearer Shares in Hungary? Remarks on Mandatory and Default Rules in Hungarian Company Law’, European Company Law, 16(3), pp. 95–100. Veress, E. (2024a) ‘Állandó és változó elemek a kft. szabályozásában. 2. rész: Törzsbetét, üzletrész’, Gazdasag es Jog, 2024/11–12, pp. 3–10. Veress, E. (2024b) ‘A társasági jog elmélete és a társaságok általános jellemzői’ in Fegyveresi, Zs. (ed.) Roman tarsasagi jog, 3rd edn. Cluj-Napoca: Forum Iuris. Žitňanská, L. (2022) ‘Účinky prevodu obchodného podielu a akcie medzi zmluvnými stranami, voči spoločnosti a voči veriteľom’ in Havel, B., Nevolná, Z. (eds.) Převody obchodnich podilů a akcii. Praha: Wolters Kluwer ČR, pp. 137–147. Zvára, M. (2017) ‘Nabytí podílu od neoprávněného ve společnosti s ručením omezeným na základě smlouvy o převodu podílu’, Obchodněpravni revue, (7–8), pp. 193–198.